Huangqi Decoction Alleviates Alpha-Naphthylisothiocyanate Induced Intrahepatic Cholestasis by Reversing Disordered Bile Acid and Glutathione Homeostasis in Mice - Wu, Jia-Sheng; Li, Yi-Fei; Li, Yuan-Yuan; Dai, Yan; Li, Wen-Kai; Zheng, Min; Shi, Zheng-Chun; Shi, Rong; Wang, Tian-Ming; Ma, Bing-Liang; Liu, Ping; Ma, Yue-Ming (Frontiers in Pharmacology, 2017)
Intrahepatic cholestasis is a serious symptom of liver disorders with limited therapies. In this study, we investigated the efficacy of Huangqi decoction (HQD), a two-herb classic traditional Chinese medicine, in the treatment of alpha-naphthylisothiocyanate- (ANIT) induced intrahepatic cholestatis in mice. HQD treatment ameliorated impaired hepatic function and tissue damage. A metabolomics study revealed that the endogenous metabolites that were significantly affected by HQD were related to bile acid (BA) biosynthesis and glutathione metabolism pathways. HQD treatment decreased the intrahepatic accumulation of cytotoxic BAs, normalized serum BA levels, and increased biliary and urinary BA excretion. Additionally, HQD restored the hepatic glutathione content and suppressed ROS in cholestatic mice. Protein and gene analysis revealed that HQD increased the expression of the hepatic metabolizing enzymes Cyp2b10 and Ugt1a1, and that of the multidrug resistance protein 2 (Mrp2), Mrp3, and Mrp4, which play crucial roles in BA homeostasis. Further, HQD increased the protein expression of glutamate-cysteine ligase, which is involved in the synthesis of glutathione. Importantly, HQD increased nuclear factor-E2-related factor-2 (Nrf2) nuclear translocation. In conclusion, HQD protects against intrahepatic cholestasis by reversing the disordered homeostasis of BAs and glutathione